Pesticides in the Environment and Food Commodities: An Investigation of Pesticide Transport in Soil and Groundwater in the Most Vulnerable Site of Bangladesh - Yunus, A.; Anwar, Faisal (Springer-Verlag, 2011)
We investigate the behaviour and fate of pesticides in soil and groundwater in one of the most vulnerable site of Bangladesh, name Rangpur sadar thana. Leaching Potential Index (LPI) of sixty nine sites is calculated and one most vulnerable site is selected. Six soil samples are collected from different depths of soil and analysed for pesticide residues using Gas Chromatograph (GC) and High Performance Liquid Chromatograph (HPLC). Tests are carried out for most recently used pesticide fenitrothion as well as other pesticides of organophosphorous, carbamate and organochlorine group. No peak is detected in chromatograms which resembles to the retention time of these pesticides. The transport behaviour of pesticides for the chosen site is also investigated by MODFLOW to forecast on the contamination potential of different pesticides. Simulation results reveal that low persistent pesticides fenitrothion and malathion are environment friendly, as percentage remaining is very small in different depths. In contrast diazinon, chlorpyrifos, cypermethrin of organophosphorous; carbofuran and carbaryl of carbamate; and heptachlor and endosulfan of organochlorine pesticides could reach groundwater because their percentage remaining in the groundwater level is high. However, this study revealed that due to the general use of low persistent organophosphorous pesticides there is no significant contamination in soil and groundwater of Rangpur sadar thana.